RELATIONSHIPS BETWEEN OSTEOCALCIN LEVEL AND HORMONAL METABOLIC DISORDERS IN TYPE 2 DIABETIC MEN WITH VARIOUS DEGREES OF OBESITY (LITERATURE REVIEW AND OWN RESEARCH) - Kovalchuk A. V.; Prybyla O. V.; Kushnareva N. M.; Zinich O. V.; Kovalchuk V. M.; Shyshkan-Shyshova K. O. (World Science, 2021)
The bone hormone osteocalcin is formed by osteoblasts and is partially released into the bloodstream during bone resorption, being a biomarker of bone remodeling. Osteocalcin also plays an important role in the endocrine regulation of metabolic and energy processes in the body and in their coordination. Osteocalcin uses a feedback mechanism to regulate insulin secretion, insulin sensitivity of peripheral tissues, and adipokine levels. In general, the secretion of osteocalcin and insulin are important factors in the formation of hormonal-metabolic phenotype, body composition, determination of regional distribution and metabolic activity of both bone and adipose tissue.The aim of this study was to establish the relationship between osteocalcin concentration and hormonal changes in men with type 2 diabetes with and without obesity on the background of involutive changes. Results. 64 men with type 2 diabetes, older than 50 years, were divided into 2 groups by BMI: 1) non-obese, BMI <30 kg / m2 (n = 31); 2) -obese, BMI ≥ 30 kg / m2 (n = 33). Lower levels of insulin secretion (lower serum C-peptide and insulin levels) were observed in non-obese patients in the absence of a compensatory increase in proinsulin levels. It can be assumed that the increase in the concentration of osteocalcin in group 1 is compensatory, although it does not have a significant effect on blood glucose levels. However, it may have a protective effect on the severity of insulin resistance syndrome and related metabolic disorders. Lower levels of osteocalcin in the obese group were associated with a higher degree of insulin resistance and insulin secretion. There was no significant difference between the two groups in serum proinsulin levels, as well as in androgen supply, which was assessed by the levels of total testosterone, testosteronestradiol-binding globulin, and free testosterone index. Conclusion. Lower levels of osteocalcin may be a marker of an increased risk of adverse metabolic changes in obese patients with type 2 diabetes, followed by complications compared to non-overweight patients